Real-World Study of Lanreotide Autogel in Routine Practice in Patients with Gastroenteropancreatic Neuroendocrine Tumors (GEP-NETs) in Hong Kong and Taiwan - Jen-Shi Chen; Li-Yuan Bai; Hsiao-Hsiang Cheng; Stephen Lam Chan; Ji-Yan Zou; Xiaofeng Shi; Aude Houchard; Xuan-Mai Truong-Thanh; Ming-Huang Chen (Oncology and Therapy)
Abstract Introduction There is a lack of data on the efficacy, effectiveness, and safety of lanreotide autogel in patients with gastroenteropancreatic neuroendocrine tumors (GEP-NETs) of Chinese ethnicity. This noninterventional, retrospective study evaluated the effectiveness and safety of lanreotide autogel in patients of Chinese ethnicity with GEP-NETs in clinical practice. Methods Patients’ charts were abstracted from five hospitals in Hong Kong and Taiwan (July–September 2021), where lanreotide autogel is approved for treating GEP-NETs. Included patients were adults with unresectable, metastatic, or locally advanced GEP-NETs who received a first injection (index) of lanreotide autogel 120 mg between 01 January 2017 and 30 June 2020 (planned sample size: N = 30). Follow-up ran from index to a maximum of 48 (± 4) weeks or until disease progression, start of new antitumor treatment, or death. The primary endpoint was progression-free survival (PFS) rate at week 48 (±4), and secondary endpoints included PFS rate at week 24 (±4), estimated using Kaplan–Meier analyses. All analyses were descriptive. Results Of 27 patients enrolled, 22 (81.5%) had 48 weeks of follow-up. Tumors of pancreatic origin were the most common (73.9%). PFS rate was 0.96 (95% confidence interval: 0.72 − 0.99) at 24 weeks and 0.82 (0.53–0.94) at 48 weeks. Overall, 74.1% patients experienced ≥ 1 treatment-emergent adverse event; none were serious. No deaths were reported. Conclusions Lanreotide autogel was well tolerated and showed good tumor control rate in a real-world setting. These findings align with results from previous studies in Caucasian, Japanese, and Korean patients, thus supporting lanreotide autogel for treating patients with GEP-NETs of Chinese ethnicity.